The emerging European defense market - Korać Srđan; Bulatović Aleksandra (Međunarodni Problemi, 2011)
The paper deals with prospects of the developing common EU defense procurement market and policy with a view to strengthening the defense identity of the European Union as well as to promoting its external profile and international role. Despite of the European Union’s overall GDP, the Union is not considered a serious military power. The EU processes of market integration and rationalization have bypassed European defense industries, which are fragmented and increasingly losing ground to their American and some Far East Asian competitors. This has prompted calls for introducing the supranational defense procurement and defense industry policies. The analysis focuses on functioning of the European Defense Equipment Market via application of the EU Code of Conduct on Defense Procurement and reviews EU prospects for establishment of a single defense market from the policy, organizational and commercial perspectives. The authors conclude that in the long run, the voluntary intergovernmental defense procurement regime established between some EU members will open prospects of cutting national defense spending, fostering the global competitiveness of the defense industries of EU member states and building up a respectable military capacity to additionally support the Common Defense and Security Policy.